2020
DOI: 10.18632/aging.103174
|View full text |Cite
|
Sign up to set email alerts
|

Sirt1 gene confers Adriamycin resistance in DLBCL via activating the PCG-1α mitochondrial metabolic pathway

Abstract: Sirt1 is closely related to cells aging, and Sirt1 also plays an important role in diffuse large B-cell lymphoma (DLBCL). However, its mechanism remains unclear. Therefore, we investigated the mechanism of Sirt1 mediated drug-resistance in DLBCL, while the recombinant lentivirus was used to regulate Sirt1 gene expression in DLBCL cell lines. Subsequently, the effect of Sirt1 on DLBCL resistance to Adriamycin was analyzed in vitro. The results show that Sirt1 overexpression confers Adriamycin resistance in DLBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Previous studies have demonstrated that syringin regulated TLR4/NF-κB and SIRT3/PGC1α pathways. 31,32 As SIRT1 is upstream regulator of both pathways, [33][34][35] we hypothesized that syringin also could influence the expression of SIRT1. SIRT1 is expressed in all mammalian cell lines and was initially judged to be a nuclear protein.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that syringin regulated TLR4/NF-κB and SIRT3/PGC1α pathways. 31,32 As SIRT1 is upstream regulator of both pathways, [33][34][35] we hypothesized that syringin also could influence the expression of SIRT1. SIRT1 is expressed in all mammalian cell lines and was initially judged to be a nuclear protein.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the deacetylation of MFN2 by Sirt1 has been previously reported ( 22 ), the mechanisms by which Sirt1 regulates MFN2 protein expression remain unclear. Previous research has revealed that PGC-1α is a target protein of Sirt1, and that the overexpression of Sirt1 can cause an increase in PGC-1α protein expression ( 36 ). Furthermore, PGC1α can regulate Mfn2 transcription by binding to its promoter region ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a similar phenomenon was also observed after cryopreservation of mouse GV oocytes. Sirt1 mediated activation of Pgc-1α through Pgc-1α deacetylation (50,51), potentially regulating mitochondrial biogenesis and mitochondrial metabolism (52). Meanwhile, Pgc-1α could also activate Tfam, which is required for mtDNA transcription and mtDNA replication, through co-activation of nuclear respiratory factor 1 (Nrf1) (53).…”
Section: Discussionmentioning
confidence: 99%